Correlation Between an Exclusive Breast Feeding with Baby’s Nutritional Status Assessed at Primary Health Care, Region I in North Denpasar - Pande Putu Novi Ekajayanti; Pande Putu Indah Purnamayanthi (STRADA : Jurnal Ilmiah Kesehatan, 2019)
According to data from the Basic Health Research of Indonesia (Riskesdas), exclusively breastfed babies has reached only 15.3% in 2010. While in Denpasar, its level fell from 62.2% in 2007 to 56.2% in 2008 for infants aged 0-6 months. This study aims to find out an exclusive breastfeeding given in infants, assessing infant’s nutritional status, and the correlation between an exclusive breastfeeding with infant’s nutritional status at Primary Health Care, Region I in North Denpasar. This research used a descriptive correlative method. Subjects were given exclusively breastfed for totally 45 respondents. This type of sampling using a purposive sampling. Statistical analysis was done by Chi-Square. Respondents were breastfed exclusively has higher normal nutritional status for about 51.1% compared with those whose was not given, showing only 15.6%.